The role of labor-management councils in the changing world of work - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations, 2003)
Attributes of a fundamentally new economy, made possible by information technology and the globalizing economy are explored. Competition will intensify as consumers gain direct access to sources worldwide. As a result, average organization size will fall due to firms resorting to automation of business processes, re-engineering, re-organization towards a flatter organization, and far-reaching use of downsizing strategies, including outsourcing. Virtual corporations and flexible work arrangement, including telecommuting, are starting to replace fixed offices and long-term employment contracts. The new century is also deemed to see the rise of an elite group of workers called the multi-skilled, knowledge workers, and the decline in the relevance of the middleman in business transactions.